In the fifth - Cox, Pamela; Enid, Blyton (London : Hodder childern books, 2019)
Games, lessons, quarrels and tricks all form part of a lively term, but the biggest event of all is the fifth form pantomime, written, acted and produced entirely by the girls. It generates a lot of fun, but also a surprising amount of trouble
Keywords: English - Teenager fiction book